2021
DOI: 10.3390/microorganisms9040790
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Lipid Remodeling in Leishmania Parasites

Abstract: Leishmania parasites efficiently develop resistance against several types of drugs including antimonials, the primary antileishmanial drug historically implemented. The resistance to antimonials is considered to be a major risk factor for effective leishmaniasis treatment. To detect biomarkers/biopatterns for the differentiation of antimony-resistant Leishmania strains, we employed untargeted global mass spectrometry to identify intracellular lipids present in antimony sensitive and resistant parasites before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 68 publications
3
13
0
1
Order By: Relevance
“…Nonetheless, our understanding of the specific lipid changes during the development of antimony resistance is still limited. Gutierrez Guarnizo et al (2021) reported, on resistant phenotypes of L. tropica, a downward trend in phospholipids, particularly in phosphatidylcholine and a shift to an upward trend in TAGs and long-chain fatty acids in susceptible phenotypes [43]. Among the studied clones, clone 32-3, which was the least sensitive to Sb(III) contained the lowest content of phospholipids as well as TAG and its long-chain fatty acids.…”
Section: Discussionmentioning
confidence: 93%
“…Nonetheless, our understanding of the specific lipid changes during the development of antimony resistance is still limited. Gutierrez Guarnizo et al (2021) reported, on resistant phenotypes of L. tropica, a downward trend in phospholipids, particularly in phosphatidylcholine and a shift to an upward trend in TAGs and long-chain fatty acids in susceptible phenotypes [43]. Among the studied clones, clone 32-3, which was the least sensitive to Sb(III) contained the lowest content of phospholipids as well as TAG and its long-chain fatty acids.…”
Section: Discussionmentioning
confidence: 93%
“…Balanced “calcium metabolism” (9 genes) and “antioxidant response” (11 genes) can participate in mediating the oxidative stress typically induced by the antimony and promote the drug inactivation via thiol metabolism 52 . Optimized “energy metabolism” (9 genes) could supply the high-energy cost required by the antioxidant response activation and other drug depuration mechanisms 10 . Since the flagellar movement is associated with a high-energy cost, the decrease in “flagellar components” (8 genes) can contribute to optimizing energy metabolism by conserving ATP 24 .…”
Section: Resultsmentioning
confidence: 99%
“…There are indications that resistance to antimony is a complex process that involves changes in the genome, metabolome, and lipid remodeling 10 – 13 . Antimony-resistant parasites have been shown to combat the drug in several ways: reducing drug uptake by downregulation of the aquaglyceroporin 1 transporter; optimizing the antioxidant response by thiol metabolism activation; tuning the energy metabolism to fuel the high energy demanded by the antioxidant response; using the thiols as drug sequesters to form thiol-metal complexes; and increasing the efflux of thiol-metal complexes via exocytosis by overexpression of ABC transporters 14 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides serving as an energy source and building blocks of the membrane, lipids are implicated in parasite-host interaction and pathogenesis [ 9 , 10 , 11 ]. Drugs such as miltefosine and antimony induce lipid perturbations which contribute to the development of drug resistance in Leishmania parasites [ 12 , 13 ]. Notably, Leishmania parasites produce different types of sterols from humans, making the sterol synthesis pathway an attractive pharmacological target [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%